Einschätzungen von Hauptschullehrern zu basalen Fähigkeiten ihrer Schüler am Beginn der Sekundarstufe I (mathematica didactica, 2007)
In the current discussion on teaching mathematics there exists a consensus that it’s very important for teachers to have sufficient information about the (pre-)knowledge of their pupils. But there exist clear hints too, that teachers are not always able to do good assessments of pupils’ competencies. The study presented here tries to find out more about the assessments of teachers relating to elementary competences of the pupils at the beginning of secondary school. Therefore mental arithmetic competencies of fifth grades pupils are examined with classroom tests (n = 185) on the one side and clinical interviews on the other side. Additionally a teacher’s questionnaire (n = 112) is developed to find out more about how teachers assess pupils’ knowledge.